Pengembangan Media Belajar Planetarium Toys Sebagai Peningkat Pemahaman Siswa Kelas VI Materi Tata Surya Bidang Studi IPA - Azzahra, Nadya Kinanti; Rofian, Rofian; Budiman, Muhammad Arief (Indonesian Research Journal on Education, 2023)
This research is motivated by the results of interviews with grade VI teachers of SDN Manyaran 01 who stated that SDN Manyaran 01 experienced limited learning media. The purpose of this study was to develop Planetarium Toys media to improve student understanding of solar system material in grade VI SDN Manyaran 01. This type of research uses Research and Development (R&D). Development with 5 stages,namely (1) Analysis, namely identifying existing problems at SDN Manyaran 01, (2) Design, designing learning media according to the needs of students and educators, (3) Development, developing learning media Planetarium Toys designed as needed, (4) Implementation, conducting field trials with the object of grade VIstudents using Planetarium Toys media in the learning process, (5) Evaluation, perfecting the product after conducting trials. The results showed that Planetarium Toys had an average percentage of the results of one media expert validation of 100% with the predicate (very feasible). While the validation of the second mediaexpert with a percentage of 94% can be said (very feasible) and the material expert validation has apercentage result of 86% so the media is declared (very feasible). Meanwhile, the results of the practicality test were obtained from the results of the class teacher's response of 81% (very feasible) and the overall student response had a result of 86% (very feasible). These results show that Planetarium Toys media can be a tool to increase the understanding of grade VI students in solar system material. Based on the results of the study, the researcher concluded that Planetarium Toys media provides a solution to the problem of limited learning media at SDN Manyaran 01. Planetarium Toys media is feasible to use based on the results of the media expert questionnaire, material experts, educators, and student questionnaires.